Experimental investigation on spring-back deformation during autoclave curing of parabolic antenna reflectors. (December 2018) - Shah, Dhaval B.; Patel, K.M.; Patel, Arvind I.; Pariyal, Vishwajit; Joshi, Shashikant J.
Abstract: High dimensional fidelity is the primary challenge for the large size carbon fiber reinforced polymer (CFRP) antenna reflectors used in space applications. Selection of crucial process parameters governs dimensional control of a composite product. In this paper, the influence of the mould materials, curing cycle, lay-up sequence and laminate thickness on spring-back deformation during autoclave curing is investigated by fabricating a large number of parabolic reflectors using the unidirectional prepreg system. The non-contact type accurate 3D scanning technique is used to measure the dimensions of the parabolic antenna reflectors. In the present work, an experimental approach is adopted for the determination of a combination of process parameters which gives minimum spring-back deformation. The results reveal that the spring-back deformation of parabolic reflectors is significantly affected by the mould material and laminate thickness, whereas the lay-up sequence and curing cycle do not have a significant effect.